Analisis Pengaruh Faktor Sosial Ekonomi Terhadap Pengeluaran Konsumsi Rumah Tangga: Analysis of the Influence of Socio-Economic Factors on Household Consumption Expenditures - Ahmad Egi Pratama; Laili Huriati; Sahar (Pinus Publishing, 2025)
The Plambik Village community has a fairly large population, namely 8928 people with 2395 households. The area of Pambik Village is 1,095.03 KM2, with a population of 8928 people with 2395 households. The people's jobs are divided into several sectors such as agriculture, trade, civil servants and other private employees. The age of the respondents used was between 25 years to 64 years, and their education level ranged from elementary school to university. The education level of the respondents was mostly high school or equivalent with the average job being farmers. Community income levels start from IDR 500,000 to IDR. 2,500,000. so the average income based on type of work is IDR 1,500,000 to IDR. 2,000,000. The correlation test education result variable is 0.768, which means that the level of education or knowledge influences people's consumption power or education influences household consumption styles. Education can change a person's attitudes and behavior in meeting their life needs. The higher the level of education, the more likely it is that you will have a higher level of income. High and quality education can increase human resources, so that income and energy consumption will be well controlled.